REMEDIATION CAPACITY AND GROWTH RESPONSES OF Platanus orientalis L., Eucalyptus camaldulensis Dehn., and Populus nigra L. TO DIFFERENT LEVELS OF LEAD AND CHROMIUM IN CONTAMINATED SOIL - J. F. Amedi; R. O. Rasheed; D.A. Ibrahim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was conducted to evaluate the effect of contaminated soil with lead and chromium using three species of trees Platanus orientalis, Eucalyptus camaldulensis, and Populus nigra as a remediation tool which considers as a priority restoring method to keep healthy soil which support life system for all organisms. The experiment was conducted with three concentrations of Pb (200,400, and 600 mg.kg-1) and three levels of Cr (100, 200, and 300 mg.kg-1) along with control. The results reveals that root dry weight for orientale plane and poplar tree were reduced meanwhile, eucalyptus showed significant increase at 200 and 400 mg.kg-1 of lead. Shoot dry weight of poplar revealed a stimulatory effect (187.26, and 193.5 g) at 200 and 400 mg.kg-1 of lead respectively. Chlorophyl content decreased significantly linearly with the increasing the concentration of Pb and Cr. At the same time, proline content showed the highest values ((76.53, 35.325, and 45.020 µmoles. g-1) at 300 mg.kg-1 of chromium in oriental plane, eucalyptus, and poplar respectively. Generally, the root system accumulates more Pb and Cr than leaves in which the bioaccumulation factor was < 1 for all species similarly the translocation factor except in eucalyptus (1.135, 1.013, and 1.018) at control, 200, and 400 mg.kg-1 of lead respectively as well as their leaves content of lead was more than root. In conclusion the species showed differ responses to Pb and Cr.